Facial recognition using deep learning - Abdulrazak Yahya Saleh; Kirthanaa A/P Jiva Rattinami (Universitas Ahmad Dahlan, 2018)
In this article, the researcher presented the results of recognition of four emotional states (happy, sad, angry, and disgust) based on facial expressions. A deep learning method with a Convolutional Neural Network algorithm for recognizing problems has been proven very effective way to overcome the recognition problem. A comparative study is carried out using MUAD3D dataset from Faculty of Computer Science and Information Technology, Universiti Malaysia Sarawak for evaluating accuracy performance of this dataset. More discussion is provided to prove the effectiveness of the Convolutional Neural Network in recognition problems.